Dynamics of gametogenesis, embryogenesis, and larval release in a Mediterranean homosclerophorid demosponge - Riesgo, A.; Maldonado, M.; Durfort, M. (Marine and Freshwater Research, 2007)
We investigated the cycle of sexual reproduction in a Mediterranean population of Corticium candelabrum by light and electron microscopy, using non-destructive tissue sampling. Most individuals of this hermaphroditic species engaged in reproduction. The relationship between seawater temperature and gametogenesis was not straightforward. Oogenesis, characterised by a long phase of oocyte growth,was continuous, with new oocytes appearing every single month of the year. Nevertheless, maximum oocyte production coincided with declining temperatures. Likewise, spermatogenesis started in the coldest month of the year. In contrast, embryonic development and larval release were limited to a few weeks during the seasonal rise of temperature and the warmest months, respectively. Female and male gametes were located in close proximity in the mesohyl. Monociliated spermatogonia putatively derived from choanocytes, and oogonia from archaeocytes. Spermatogenesis, which strongly resembled that in higher animals, produced round spermatozoa that were provided with acrosome and anchoring system for the cilium. Mature oocytes became surrounded by a bacterial layer. Many symbiotic bacteria served for oocyte nourishment, but others were transferred to the larva. As a whole, the reproductive cycle, which also exhibited quite successful fertilisation and low mortality during embryonic development, appears finely tuned to improve the competitive ability of this sponge.